Analisis Kinetika Laju Pertumbuhan Lumpur Aktif Artificial menggunakan Karbon Aktif pada Tahap Seeding - Priyoharjo, Angga Mustofa; Prayatni Soewondo (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Textile industry WWTP systems generally use chemical and biological activated sludge. Activated sludge systems tend to require a long retention time and are less effective in degrading color. One technology that can be developed is the improvisation of activated sludge microorganisms with the addition of powdered activated carbon. This research is to develop a combination technology of powdered activated carbon addition in the seeding stage and see its effect on the growth rate of microorganisms during the seeding and acclimatization stages. The initial stage was a seeding process using liquid starter bacteria carried out in 5 reactors with a capacity of 5 L, with the dose of activated carbon addition in reactors 1, 2, 3, 4 and 5 namely 0 mg/l, 100 mg/l, 400 mg/l, 800 mg/l and 1000 mg/l and a blank reactor with only activated carbon without the addition of starter bacteria. Parameters observed during the study were DO, pH, MLSS and COD values. The seeding process is carried out for 28 days until the MLSS reaches 2000 mg/l, followed by an acclimatization stage which is carried out for 30 days with a COD value set at 1000 mg/l using an artificial substrate. At the seeding stage, the optimal reactor was R5, which was based on the increase in MLSS over time and the kinetics of growth rate as a µmax value of 0.2179 days⁻¹ and acclimatization stages 1 and 2 with µmax values of 0.0853 days⁻¹ and 0.0959 days-1, respectively.